2021
DOI: 10.1002/advs.202100215
|View full text |Cite
|
Sign up to set email alerts
|

Type‐I Energy Level Alignment at the PTCDA—Monolayer MoS2 Interface Promotes Resonance Energy Transfer and Luminescence Enhancement

Abstract: Van der Waals heterostructures consisting of 2D semiconductors and conjugated molecules are of increasing interest because of the prospect of a synergistic enhancement of (opto)electronic properties. In particular, perylenetetracarboxylic dianhydride (PTCDA) on monolayer (ML)‐MoS2 has been identified as promising candidate and a staggered type‐II energy level alignment and excited state interfacial charge transfer have been proposed. In contrast, it is here found with inverse and direct angle resolved photoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 66 publications
(100 reference statements)
3
69
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Depending on their density on the substrate and on their physico-chemical characteristics, physisorbed moieties can introduce localized electronic states, [10][11][12] dispersive bands, 7 or a combination thereof. [13][14][15] The electronic structure of the interface results from the level alignment between the organic and inorganic components [16][17][18][19][20] and the hybridization between their electronic wave-functions. 15,[21][22][23][24] As both these effects depend on the intrinsic nature of the building blocks, the need for systematic analyses on the electronic structure of hybrid systems are in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Depending on their density on the substrate and on their physico-chemical characteristics, physisorbed moieties can introduce localized electronic states, [10][11][12] dispersive bands, 7 or a combination thereof. [13][14][15] The electronic structure of the interface results from the level alignment between the organic and inorganic components [16][17][18][19][20] and the hybridization between their electronic wave-functions. 15,[21][22][23][24] As both these effects depend on the intrinsic nature of the building blocks, the need for systematic analyses on the electronic structure of hybrid systems are in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 , 15 ] Recent works have shown that combinations of suitable materials allow fabrication of both type‐I and type‐II organic/TMD heterojunctions. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] Qiao et al. fabricated heterostructures consisting of MoSe 2 monolayers (bandgap, E g : 1.55 eV) and pentacene ( E g : 1.8 eV).…”
Section: Introductionmentioning
confidence: 99%
“…fabricated a hybrid structure composed of MoS 2 monolayers ( E g : 2.11 eV) and perylenetetracarboxylic dianhydride ( E g : 2.55 eV), which exhibited a twofold‐enhanced visible‐light PL yield of MoS 2 monolayer. [ 3 ] Since many visible‐light‐fluorescent organic materials are available, [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] efforts to find materials for type‐I organic/TMD heterojunctions and their careful characterizations should deserve considerable attention for both fundamental science and device applications. Also, systematic investigations to study interfacial excitonic behaviors in such hybrid systems should be established.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Depending on their density on the substrate and on their physico-chemical characteristics, physisorbed moieties can introduce localized electronic states, [10][11][12] dispersive bands, 7 or a combination thereof. [13][14][15] The electronic structure of the interface results from the level alignment between the organic and inorganic components [16][17][18][19][20] and the hybridization between their electronic wave-functions. 15,[21][22][23][24] As both these effects depend on the intrinsic nature of the building blocks, the need for systematic analyses on the electronic structure of hybrid systems are in high demand.…”
Section: Introductionmentioning
confidence: 99%